Global surgery - socioeconomic and geographic maldistribution of surgical resources - Dell, Angela June (Department of Surgery, 2017)
Surgery is an indispensable part of any health system and improving access to safe surgery remains a challenge in the developing world. Surgery is emerging as a priority in global health, unfortunately information around the burden of surgical diseases or the available surgical resources is limited. South Africa is an Upper Middle Income Country (UMIC) and currently provides reasonable surgical services, however these services vary across regions, between urban and rural settings, as well as between public and private hospitals. There is no reliable data regarding the available surgical resources in South Africa, namely surgical beds, operating theatres and surgeons. These variables are essential in developing a National Surgical Plan to address the burden of surgical disease, however they are limited in the information they provide they provide regarding surgical capacity and need to be assessed in context with more robust indicators. This aim of this study was to quantify some of the specific surgical resources as identified by the World Health Organization (WHO) and the Lancet Commission. This research will contribute to the growing body of research regarding global surgery in South Africa and attempt to provide an analysis of metrics used to evaluate surgical systems. The research hypothesis was that the surgical resources in South Africa were limited, and that surgeons, theatres and hospital beds per capita are inadequate compared to developed countries and do not meet global recommendations. This involved a descriptive analysis of surgical resources and included the total number of hospitals, of hospital beds, the number of surgical beds, the number of general surgeons (specialist and non-specialist), and the number of functional operating theatres in South Africa. The surgical resources were analysed, both according to province and district, and a comparison was performed based on the population density. A comparison of the public and private facilities was undertaken with regard to the total numbers, as well as per population density. Lastly, a comparison was performed with other high and low income countries around the world. The results showed one hospital per 100 000 population, 186.64 hospital beds, 41.55 surgical beds, 1.78 specialist general surgeons, 2.90 non-specialist general surgeons, and 3.59 operating theatres per 100 000 people in South Africa. These numbers fell far below international recommendations, as well as developed countries such as the United Kingdom (UK) and United States of America (USA). Surgical resources were concentrated in metropolitan areas, and there were differences between the public and private sectors, with private hospitals having a greater number of surgical beds and operating theatres per population than public hospitals. These data indicated how surgical providers and basic infrastructure were distributed in South Africa, which will allow more accurate planning by government policymakers. Recommendations need to be tailored according to each sector as the needs of the patients and resources available are different. There is a need to acknowledge the major shortage of healthcare providers with implementation of the National Health Insurance (NHI). There is a need for validated instruments to accurately collect data and for reliable electronic information sharing which will improve data collection and analysis between rural and urban areas. Existing resources need to be utilized more effectively. These results showed that regional hospitals lack both specialist and non-specialist general surgeons. The international consensus was that performing surgery at district level hospitals improved access and lowered cost, however this will need recruitment of additional skilled personnel and infrastructure in order to support surgery at this level. This national audit has provided much needed data on the some of the available surgical resources may influence critical decision-making about funding distribution, resource and training post allocations, as well as address inequalities in service delivery.